Influence Readiness Study on Learning Outcomes Economy Students in Phase E (Independent Curriculum) with Environment Study as variable mediation at UNESA Labschool High School 1 - Farid, Muhammad Miftah; Martha Mahendra, Angga; Ernie Munikasari, Lavita (Universitas Negeri Surabaya, 2023)
Study This aims To analyze the influence of readiness learning and environment Study to results Study economy in a way Partial nor simultaneous. Sample study These are 400 students in phase E at UNESA Labschool High School 1. Data collection techniques used are questionnaires and documentation. Method the analysis uses the technique of multiple linear regression. Research results show that readiness learning, environment Study can explain the results Study. However variable readiness Study will have more influence on the results learn, if strengthened with an environment Study as variable mediation.